Euphorbia tirucalli leaf extract induces apoptosis and inhibits cell migration in HSC-3 tongue cancer cells - Ongkiwijaya, Imelda; Amtha, Rahmi; Sandra, Ferry; Rizal, Muhammad I.; Widyarman, Armelia S.; Lestari, Widya (Faculty of Dentistry, Hasanuddin University, indonesia, 2025)
Objective: Oral squamous cell carcinoma (OSCC) of the tongue is a highly aggressive cancer known for its unfavorable prognosis, largely due to its resistance to conventional therapies. Euphorbia tirucalli, a medicinal plant rich in bioactive compounds, has demonstrated potential anticancer effects. However, there is a scarcity of research on the impact of E. tirucalli leaf extract (ETLE) on tongue cancer. This study investigated the effect of ETLE on cell viability, apoptosis, and cell migration in human squamous cell carcinoma (HSC)-3 tongue cancer cells. Material and Methods: ETLE was prepared using the maceration technique. HSC-3 cells were treated with ETLE at concentrations of 2%, 10%, and 50%. Cell viability was evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, while apoptosis was analyzed through the sub-G1 assay. A cell migration assay was also conducted to assess the effect of ETLE on cell migration. Results: ETLE significantly reduced HSC-3 cell viability in a concentration-dependent manner. ETLE increased the percentage of apoptotic cells in a concentration-dependent manner as well. Additionally, ETLE significantly inhibited cell migration, with the 50% ETLE-treated group showed minimal migration, comparable to the doxorubicin-treated group. Conclusion: ETLE could exhibited significant cytotoxic effects on HSC-3 tomgue cancer cells by inducing apoptosis and inhibiting migration, suggesting its potential as an anti-cancer agent for tongue cancer cell